2002
DOI: 10.1007/s00134-002-1431-2
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine-induced hyperglycemia does not increase cortical lactate in brain-injured rats

Abstract: Norepinephrine and dopamine significantly increased pericontusional glucose concentrations which did not elevate extracellular lactate and aggravate underlying posttraumatic edema formation. In addition to possibly increased facilitated endothelial glucose transport, the elevated extracellular to blood glucose ratio suggests a passive concentration- and pressure- dependent entry via a damaged blood-brain barrier. This might contribute to the observed reversible increase in extracellular glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Thus, elevating MABP in the early posttraumatic phase could have contributed to increased vasogenic edema formation via sustained hydrostatic pressure as often criticized by proponents of the "Lund" concept in the treatment of head injury (2). In this context, increases in pericontusional extracellular glutamate and glucose during norepinephrine infusion early after CCI (11,47) are suggestive of uncontrolled passive penetration. Concentration dependently, norepinephrine acts as a pro-oxidative or anti-oxidative agent (25).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, elevating MABP in the early posttraumatic phase could have contributed to increased vasogenic edema formation via sustained hydrostatic pressure as often criticized by proponents of the "Lund" concept in the treatment of head injury (2). In this context, increases in pericontusional extracellular glutamate and glucose during norepinephrine infusion early after CCI (11,47) are suggestive of uncontrolled passive penetration. Concentration dependently, norepinephrine acts as a pro-oxidative or anti-oxidative agent (25).…”
Section: Discussionmentioning
confidence: 92%
“…Although we did not assess brain levels of glucose in the current study, we speculate that the interstitial levels were increased in our CCI rats administered glucose. Norepinephrine infusion in rats with CCI increases blood glucose (from 8.6 to 12.6 mmol/L) and extracellular glucose (from 1.3 to 4.8 mmol/L) concentrations without altering edema formation (Stover et al, 2002), and it has been reported that extracellular concentrations of glucose are significantly increased during transient periods of unintentional hyperglycemia in TBI patients (Diaz-Parejo et al, 2003). The latter authors also reported no change in interstitial concentrations of pyruvate, lactate, glutamate or glycerol with episodes of moderate hyperglycemia (blood levels of 12-15 mmol/L), although lactate levels increased during episodes of more pronounced (>15 mmol/L) hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…More recently it was reported that induction of hyperglycemia prior to moderate CCI injury in mice did not adversely affect cerebral edema, behavioral outcomes or histopathology, whereas chronic hyperglycemia in rats actually reduced CCI-induced cerebral edema and a post-injury insulin therapy to lower high blood glucose increased cerebral edema (Hill et al, 2010). To date, there is no evidence that post-CCI elevations in plasma glucose will exacerbate histopathology or worsen outcomes (Cherian et al, 1998a; Stover et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kinoshita and associates showed that although acute post-traumatic dextrose treatment increased lesion area only slightly, a significant infiltration of neutrophils was seen following fluid percussion injury (FPI; Kinoshita et al, 2002). In contrast, the results of several experimental studies investigating hyperglycemia following TBI did not support adverse effects on brain damage (Gurevich et al, 1997;Hill et al, 2010;Stover et al, 2002). Clinical studies, however, show that hyperglycemia at admission is associated with poor neurological outcomes and mortality following severe TBI, both in pediatric (Melo et al, 2010;Smith, et al, 2012) and adult patients ( Jeremitsky et al, 2005;Pecha et al, 2011).…”
Section: Introductionmentioning
confidence: 87%